Real-World in Science Learning : An Science, Technology, Society (STS)-Based Science E-Module to Enhance Critical Thinking Skills - Muhasabah, Brilian Aura; Supeno, Supeno; Yusmar, Firdha (Jurnal Paedagogy, 2025)
This study aims to develop a valid, practical, and effective STS-based science e-module to enhance critical thinking skills in supporting the science learning process. This research used Research and Development with a ADDIE model. The subject of this research were seventh grade students at MTsN 1 Jember. The data collection is done using primary and secondary data. Primary data include validity score, practicality score, and effectiveness score. Secondary data include interviews, observation, and documentation. The data analysis technique used in this research were validity test, practicality test, and effectiveness test. The results of the validity analysis show a category of very valid with a percentage of 89.4% based on validation sheets covering content and construct validation. The practicality analysis obtained from the implementation during the science learning process achieved a convenient category with a percentage of 92%. With an N-Gain score of 0.66 and a medium category, the e-module's effectiveness in assessing the development of critical thinking skills was determined by the results of the pre-test and post-test. Additionally, the effectiveness analysis data from student response questionnaires show a very positive category with a percentage of 83%. Thus, an STS-based science E-Module effectively enhances critical thinking skills and suitable for junior high school learning by connecting science concepts with real-world phenomena.